The Influence of al-Ghazali’s Theological Philosophy in the Malay Archipelago: Pengaruh Karya-karya Teologi dan Falsafah al-Ghazali di Kepulauan Nusantara - Ahmad Nabir Amir; Tasnim Abdul Rahman (Senarai: Journal of Islamic Heritage and Civilization, 2025)
The article analyses the influence of Imam al-Ghazali’s (450-505/1058-1111) religious ideals in the Malay Basin particularly through his works Ihyā’ ‘Ulūm al-Dīn, Mi‘rāj al-Sālikīn, Bidāyah al-Hidāyah, Ma‘ārij al-Quds fī Madārij Ma‘rifat al-Nafs, al-Mustasfa and al-Madnun bihi ‘ala Ghayr Ahlih. The highly charged and popularity of his works come from various forms of its translated versions in the hand of Malay theologians working on its elucidation such as Sayr al-Sālikīn and Hidāyah al-Sālikīn by ‘Abd al-Samad al-Falimbani (1704-1789) and concise translation of Minhāj al-‘Ābidīn by Shaykh Daud al-Fatani. The paper situates his works in the wider context of Sunni-Islam held by the Malays and its burgeoning cultural and intellectual tradition, far-reaching intensity of activism and da‘wah and idealism widely disseminated in the regions. The study is based on qualitative method in the form of library and literature survey using inductive and deductive method. Data and materials were derived from selected primary and secondary sources and analysed by way of descriptive, analytical, empirical, hermeneutical and historical approaches. The finding reveals that the nuances of al-Ghazali’s corpus were well articulated in the Malay world developed through compelling theological and philosophical works that defend its significance values, norms, legality, ethics, metaphysics, logic and virtues and its classic synthesis of shariah and tasawuf and its spiritual illumination and articulation in the mozaic of contemporary Malay worldview and tradition.